How will an integrated sustainability tool contribute to strategy making? - Lindqvist, Sanna (2019)
The demand on companies from various stakeholders, such as customers and suppliers, to report impacts and sustainability efforts creates a need for sustainability reports to integrate the financial, environmental and social perspectives of a company. International research has during recent years focused on developing sustainability tools for measuring economic, social and environmental dimensions. To approach the challenges of sustainability, challenges such as climate change and emissions of greenhouse gases, an integrated assessment for companies is required, in order to provide guidance for decision-making.